2019
DOI: 10.1158/2159-8290.cd-18-1314
|View full text |Cite
|
Sign up to set email alerts
|

Naïve T-cell Deficits at Diagnosis and after Chemotherapy Impair Cell Therapy Potential in Pediatric Cancers

Abstract: Translational data on chimeric antigen receptor (CAR) T-cell trials indicate that the presence of naïve T cells in the premanufacture product is important to clinical response and persistence. In anticipation of developing CAR trials for other tumors, we investigated the T-cell distribution from children with solid tumors and lymphomas at diagnosis and after every cycle of chemotherapy. We found that patients with T cells enriched for naïve and stem central memory cells expanded well in vitro , but the majorit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
143
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 192 publications
(159 citation statements)
references
References 27 publications
10
143
0
3
Order By: Relevance
“…In CLL, trials have shown that effectiveness of the CD19 directed CAR‐T is dependent on the intrinsic T‐cell function itself . Similar observations on intrinsic T‐cell factors affecting CAR‐T efficacy have been recently made in the pediatric population as well . Patients with robust T‐cell proliferation and activation had improved CAR‐T responses compared to patients without good responses.…”
Section: Efficacy Of Car‐t In Hematologic Malignanciessupporting
confidence: 53%
See 1 more Smart Citation
“…In CLL, trials have shown that effectiveness of the CD19 directed CAR‐T is dependent on the intrinsic T‐cell function itself . Similar observations on intrinsic T‐cell factors affecting CAR‐T efficacy have been recently made in the pediatric population as well . Patients with robust T‐cell proliferation and activation had improved CAR‐T responses compared to patients without good responses.…”
Section: Efficacy Of Car‐t In Hematologic Malignanciessupporting
confidence: 53%
“…been recently made in the pediatric population as well. 26 Patients with robust T-cell proliferation and activation had improved CAR-T responses compared to patients without good responses. Given the average age of the population with CLL the intrinsic T-cell response is variable and thus effects outcome (Table 1).…”
Section: Similar Observations On Intrinsic T-cell Factors Affecting Cmentioning
confidence: 98%
“…T cells differentiate in a progressive manner from naive T cells (T N ) →T stem cell memory (T SCM ) →T central memory (T CM ) →T effector memory (T EM ) and ultimately terminally differentiated effectors (T EFF ) . Cancer patients frequently are depleted of T N and early memory subsets, which have a superior capacity to proliferate and persist, and develop a reciprocal accumulation of terminally differentiated T EM /T EFF cells. These later subsets are prone to apoptosis and incapable of sustained proliferation.…”
Section: Therapeutic Resistance To Tcr‐based Cancer Immunotherapiesmentioning
confidence: 99%
“…They are, in short, incapable of expanding to the magnitude required to induce clinically apparent tumor regression. This situation is compounded in many solid cancer patients by the routine use of cytotoxic chemotherapy and radiation therapy which serves to deplete less‐differentiated T cell subsets . Lastly, the microenvironment of many cancers is enriched in immunosuppressive cell subsets, including T regulatory cells, aberrantly matured myeloid cells, and immunosuppressive populations of fibroblasts …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation